Antibacterial 3D bone scaffolds for tissue engineering application. Issue 4 (19th September 2018) - Pant, Jitendra; Sundaram, Jaya; Goudie, Marcus J.; Nguyen, Dieu Thao; Handa, Hitesh
Abstract: Open bone fractures are not only difficult to heal but also are at a high risk of infections. Annual cases of fractures which result from osteoporosis amount to approximately 9 million. Endogenously released nitric oxide (NO) has been shown to play a role in osteogenic differentiation in addition to eradicating infection against a wide variety of pathogens. In the current work, antimicrobial NO releasing 3D bone scaffolds were fabricated using S ‐nitroso‐ N ‐acetyl‐penicillamine (SNAP) as the NO donor. During fabrication, nano‐hydroxyapatite (nHA) was added to each of the scaffolds in the concentration range of 10–50 wt % in nHA‐starch‐alginate and nHA‐starch‐chitosan scaffolds. The mechanical strength of the scaffolds increased proportionally to the concentration of nHA and 50 wt % nHA‐starch‐alginate possessed the highest load bearing capacity of 203.95 ± 0.3 N. The NO flux of the 50 wt % nHA‐starch‐alginate scaffolds was found to be 0.50 ± 0.06 × 10 −10 mol/min/mg initially which reduced to 0.23 ± 0.02 × 10 −10 over a 24 h period under physiological conditions. As a result, a 99.76% ± 0.33% reduction in a gram‐positive bacterium, Staphylococcus aureus and a 99.80% ± 0.62% reduction in the adhered viable colonies of gram‐negative bacterium, Pseudomonas aeruginosa were observed, which is a significant stride in the field of antibacterial natural polymers. The surface morphology and pore size were observed to be appropriate for the potential bone cell growth. The material showed no toxic response toward mouse fibroblast cells. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1068–1078, 2019. Abstract :